Barriers to Implementing a Public Library in Rural Areas in South Africa - Dickson Mdhlalose; Sedume Mashilo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This qualitative study investigates the systemic barriers hindering the realization of a public library in Kwa-Mhlanga, a rural village in Mpumalanga, South Africa. While often viewed as mere infrastructure, the library represents a vital